Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan di Waringin Group Surabaya - Rosalia Sukma Indayani; Nuryadi Nuryadi; Komarun Zaman (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the influence of organizational culture on employee performance at Waringin Group Surabaya. This research used a sample of 65 who were permanent employees and employees who had worked for at least one year at Waringin Group Surabaya. Data was collected through literature studies, questionnaires, interviews and observations. Data analysis techniques in this research include instrument testing, classical assumption testing, simple linear regression analysis, and hypothesis testing. The research results show that organizational culture has a significant effect on employee performance at Waringin Group Surabaya.